Protocol for the Stather Canadian Outcomes Registry for Chest ProcedurEs (SCOPE). Issue 1 (28th January 2021) - Tremblay, Alain; Chee, Alex C; Dhaliwal, Inderdeep; Dumoulin, Elaine; Gillson, Ashley; MacEachern, Paul R; Mitchell, Michael; Schieman, Colin; Stollery, Daniel; Li, Pen; Fortin, Marc; Tyan, Chung C; et al.
Abstract : Introduction: The Stather Canadian Outcomes registry for chest ProcedurEs (SCOPE registry) is a Canadian multicentre registry of chest procedures. Methods and analysis: The SCOPE registry is designed as a multicentre prospective database of specific bronchoscopic or other pulmonary procedures. Each procedure of interest will be associated with a registry module, and data capture designed to evaluate effectiveness of procedures on relevant patient outcomes. Participating physicians will be asked to enter data for all procedures performed in a given module. The anonymised dataset will be housed in a web-based electronic secure database. Specific modules included will be based on participating physician suggestions, capacity and consensus of the steering committee and relevance of hypotheses/research potential. Ethics and dissemination: The central registry is under approval from the Conjoint Health Research Ethics Board at the University of Calgary. We aim for registry data to lead to publication of manuscripts in international medical journals as the primary mode of dissemination. Data may also be used by local investigators for personal and/or institutional quality control purposes as well as to inform health policies. Data requests from non-participating investigators for use under ethics approved research protocols can be considered.